Heat Stress Response in Dairy Cattle - TESSALONIKA, OLGA; Indriani, Nyimas Popi; Mansyur, Mansyur (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
Indonesia is a tropical country with high ambient temperatures and humidity. In Indonesia’s hot and humid summer, dairy cows cannot dissipate enough body heat to prevent a rise in their body temperature. Increasing air temperature, temperature humidity index, and rectal temperature above a critical threshold are associated with decreased dry matter intake (DMI), milk production, and milk production efficiency. Modifications including shades and cooling fans can help dissipate body heat, lower body temperature, and increase BMI. Genetic selection for heat tolerance is possible, but continued selection for better performance without consideration for heat tolerance will result in greater susceptibility to heat stress. The nutritional requirements of dairy cows change during heat stress, and ration reformulation to account for reduced DMI, the need to increase nutrient density, alter nutrient requirements, avoid excess nutrients and maintain normal rumen function is required. Sustaining cattle performance in hot and humid climate conditions in the future will likely require increased cooling capabilities, continued advances in nutritional formulations, and the need for genetic advances that include selection for heat tolerance or identification of genetic traits that enhance heat tolerance.